Aplikasi Dgs Kesehatan Diterima Sebagai Penunjang Kerja Tenaga Kesehatan Di Puskesmas Kasihan II - Vonita Indra Andriani; Kurniawati; Tri Ariani (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Digital Government Services (DGS) Health Application. In its use, problems are still found, such as there are several menus/features that are not in accordance with needs, the DGS Health application still experiences problems/errorssuch as taking a long time to load and the server experiencing downtime, this makes it quite difficult for officers to provide services. The aim: to evaluate users of the DGS application ) using the Technology Acceptance Model (TAM) method at Kasihan II Community Health Center.Methods: This is a qualitative descriptive study, with research subjects 11 users of the DGS application (1 doctor, 3 midwives, 1 nurse, 2 medical recorders, 2 laboratory assistants, 1 pharmacist and 1 cashier).Results: The results of the evaluation of users of the DGS Health application with the 5 TAM criteria showed that: 1). Perceived usefulness/benefits (Perceived Usefulness) a). beneficial for community health centers b). 9 respondents felt they could improveofficer performance. 2). Perceived Ease of Use: All respondents felt the DGS application was easy to use. 3). Attitude Toward Using (Attitude Toward Using) a). 9 respondents had a positive attitude when using the DGS Health application because the application made work easier. b). 7 respondents had a positive attitude when the application experienced problems/errors. 4). Desire to Use (Behavioral Intention To Use) 8 respondents are interested in continuing to use the DGS Health application because the application is useful for services and easy to use. 5). Real Conditions of System/Application Usage (Actual System Usage) a). 9 respondents stated that the DGS Health application could support services b). All respondents stated that the time to use the DGS Health application was used according to the user's needs. Conclusion: Users accept the DGS Health application, in terms of use it makes it easier to provide health services and manage patient data at the Puskesmas Kasihan II.Keywords: Evaluation, Users, Applications, Health DGS, TAM